Antibiotics for preventing infection at the surgical site: Single dose vs. multiple doses - Nehad J. Ahmed; Abdul Haseeb, PhD; Abdullmoin AlQarni; Manal AlGethamy; Ahmad J. Mahrous; Ahmed M. Alshehri; Abdullah K Alahmari; Safa S. Almarzoky Abuhussain; Ahmed Mohammed Ashraf Bashawri; Amer H. Khan (Elsevier, 2023)
Background: Surgical site infections are common and expensive infections that can cause fatalities or poor patient outcomes. To prevent these infections, antibiotic prophylaxis is used. However, excessive antibiotic use is related to higher costs and the emergence of antimicrobial resistance. Objectives: The present meta-analysis aimed to compare the effectiveness of a single dosage versus several doses of antibiotics in preventing the development of surgical site infections. Methods: PubMed was used to find clinical trials evaluating the effectiveness of a single dosage versus several doses of antibiotics in avoiding the development of surgical site infections. The study included trials that were published between 1984 and 2022. Seventy-four clinical trials were included in the analysis. Odds ratios were used to compare groups with 95% confidence intervals. The data were displayed using OR to generate a forest plot. Review Manager (RevMan version 5.4) was used to do the meta-analysis. Results: Regarding clean operations, there were 389 surgical site infections out of 5,634 patients in a single dose group (6.90%) and 349 surgical site infections out of 5,621 patients in multiple doses group (6.21%) (OR = 1.11, lower CI = 0.95, upper CI = 1.30). Regarding clean-contaminated operations, there were 137 surgical site infections out of 2,715 patients in a single dose group (5.05%) and 137 surgical site infections out of 2,355 patients in multiple doses group (5.82%) (OR = 0.87, lower CI = 0.68, upper CI = 1.11). Regarding contaminated operations, there were 302 surgical site infections out of 3,262 patients in a single dose group (9.26%) and 276 surgical site infections out of 3,212 patients in multiple doses group (8.59%) (OR = 1.11, lower CI = 0.84, upper CI = 1.47). In general, there were 828 surgical site infections out of 11,611 patients in a single dose group (7.13%) and 762 surgical site infections out of 11,188 patients in multiple doses group (6.81%) (OR = 1.05, lower CI = 0.93, upper CI = 1.20). The difference between groups was not significant. Conclusion: The present study showed that using a single-dose antimicrobial prophylaxis was equally effective as using multiple doses of antibiotics in decreasing surgical site infections.